2018
DOI: 10.1002/sscp.201800106
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Terpenoid Lactones and Flavonoids from Ethanolic Extract ofAndrographis Paniculata(Burm.f.) Nees Using Liquid Chromatography/Tandem Mass Spectrometry

Abstract: Andrographis paniculata is traditionally used for the prevention and treatment of infectious diseases due to its bioactive terpenoid lactones and flavonoids. So, there is an urgent need to develop a liquid chromatography with tandem mass spectrometry method for identification and characterization of terpenoid lactones and flavonoids. The chromatographic separation of terpenoid lactones and flavonoids from crude extract was carried on Thermo Betasil C8 column (250 mm × 4.5 mm, 5 μm) using 0.1% formic acid in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
10
0
3
Order By: Relevance
“…One of the most important techniques is the combination of liquid chromatography and mass spectrometry that symbolizes a robust, sensitive, quick, and reproducible analytical method for the identification and characterization of secondary metabolites present in bioactive extracts. Several studies have reported the presence of diverse secondary metabolites from leaves, root, stem, or from whole plants of A. paniculata extracts, such as andrographolide (major compound), neoandrographolide, 14-deoxy-11, 12-didehydroandrographide and isoandrographolide [8,25,26], 14-deoxy-17-hydroxyandrographolide, 12S-hydroxyandrographolide, andrographatoside, 14-deoxy-11, 12-didehydroandrographolide, andrographolide, andrographic acid, 14-deoxyandrographolide, andrographolide derivatives, andrograpanin, bisandrographolide, skullcapflavone I, 5-Hydroxy-7,8,2′,5′-tetra-methoxyflavone 5-O-glucoside, and 7-O-methylwogon [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important techniques is the combination of liquid chromatography and mass spectrometry that symbolizes a robust, sensitive, quick, and reproducible analytical method for the identification and characterization of secondary metabolites present in bioactive extracts. Several studies have reported the presence of diverse secondary metabolites from leaves, root, stem, or from whole plants of A. paniculata extracts, such as andrographolide (major compound), neoandrographolide, 14-deoxy-11, 12-didehydroandrographide and isoandrographolide [8,25,26], 14-deoxy-17-hydroxyandrographolide, 12S-hydroxyandrographolide, andrographatoside, 14-deoxy-11, 12-didehydroandrographolide, andrographolide, andrographic acid, 14-deoxyandrographolide, andrographolide derivatives, andrograpanin, bisandrographolide, skullcapflavone I, 5-Hydroxy-7,8,2′,5′-tetra-methoxyflavone 5-O-glucoside, and 7-O-methylwogon [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The positive ion mode was much more efficient for the analysis of these kinds of compounds. Kumar et al (2018) also reported fragmentation of Andrographolide from the methanol extract of aerial parts of A. paniculata, but the fragmentation pattern differed at m/z 303 and 275 due to loss of CO in reverse Diels-Alder (RDA) [27]. The biological function of a specific diterpenoid cannot be representative for the whole class of molecules due to their diverse nature and often restricted distribution [29].…”
Section: Discussionmentioning
confidence: 99%
“…Natural products with medicinal activities can be directly isolated from plants and used in therapies or can act as a basic structure for the development of several derivatives for the development of more active and less toxic analogs [45]. Several diterpenoids including 14-deoxy-11, 12-di-dehydroandrographide, andrographolide, neoandrographolide, and isoandrographolide have been earlier reported from A. paniculata [12,[46][47][48]. Kumar et al (2018) have reported Skullcapflavone I, 5-Hydroxy-7,8,2′,5′-tetra-Methoxyflavone 5-O-glucoside and 7-O-Methylwogonin to be present in the methanolic extract of aerial parts of A. paniculata.…”
Section: Discussionmentioning
confidence: 99%
“…Several diterpenoids including 14-deoxy-11, 12-di-dehydroandrographide, andrographolide, neoandrographolide, and isoandrographolide have been earlier reported from A. paniculata [12,[46][47][48]. Kumar et al (2018) have reported Skullcapflavone I, 5-Hydroxy-7,8,2′,5′-tetra-Methoxyflavone 5-O-glucoside and 7-O-Methylwogonin to be present in the methanolic extract of aerial parts of A. paniculata.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of LC‐MS/MS with positive electrospray ionization (ESI) and multiple reactions monitoring (MRM) has proven to be an effective method for co‐analyzing multiple complex compounds in medicinal herbs [18–20] . Various chromatographic methods for the quantification of single or multiple diterpenoid lactones in A. paniculata had been developed [21–22] . However, these methods lack the ability to identify isomers and have low sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%